2021
DOI: 10.1093/rheumatology/keab691
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella and Coxiella infections presenting as systemic vasculitis: case series and review of literature

Abstract: Objectives Coxiella and Bartonella sp. display particular tropism for endothelial or endocardial tissues and an abnormal host response to infections with induced autoimmunity. We aimed, through a case series combined with a comprehensive literature review, to outline characteristics of Coxiella and Bartonella infections presenting as systemic vasculitis. Methods We retrospectively included cases of definite Coxiella and Barto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…5 Whilst Bartonella infection mimics AAV in 83% with PR3-ANCA in case series, Coxiella has been found potentially to induce vasculitis of all vessel sizes. 2 Interestingly, in this case, temporal change in PR3-ANCA titre in association with chronic Q fever suggests probable causality between infection and autoimmune phenomena.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…5 Whilst Bartonella infection mimics AAV in 83% with PR3-ANCA in case series, Coxiella has been found potentially to induce vasculitis of all vessel sizes. 2 Interestingly, in this case, temporal change in PR3-ANCA titre in association with chronic Q fever suggests probable causality between infection and autoimmune phenomena.…”
mentioning
confidence: 67%
“…Recent cases have elucidated autoimmune vasculitides associated with chronic infection. 2 This pathogen acts both as a mimic and an inducer of autoimmune disease, thereby causing a diagnostic dilemma. We report a case of chronic Q fever presenting with membranoproliferative glomerulonephritis and new anti-proteinase 3 antineutrophil cytoplasmic antibody (PR3-ANCA) positivity.…”
mentioning
confidence: 99%
“…A total of 89 cases with Bartonella IE-associated GN were included in this study (54 published case reports and case series ( 16 69 ), and 18 (17 published, 1 presented) conference abstracts ( 70 – 87 ), and four cases diagnosed at our institution). A flowchart for including cases is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The patient completely recovered after the combined use of glucocorticoids, antibiotic therapy and surgical valve repair [ 9 ]. A recent study revealed Bartonella infection could also induce immune-related glomerulonephritis with the coexistence of ANCA and cryoglobulinemia and subacute endocarditis [ 47 ]. Although there are some similarities in clinical features, the pathological changes and prognosis in different infection-related vasculitis varied from one case to another.…”
Section: Discussionmentioning
confidence: 99%